2006
DOI: 10.1001/jama.295.9.1060
|View full text |Cite|
|
Sign up to set email alerts
|

Thyroid Disease 60 Years After Hiroshima and 20 Years After Chernobyl

Abstract: 1 Subsequent surveys found a significant excess of papillary thyroid cancer but not of follicular, medullary, or anaplastic cancer.2,3 A straight line adequately describes the relationship between radiation dose and thyroid cancer incidence, relative risks are similar in males and females, and age at exposure substantively influences risk. Risk is highest for children exposed when younger than 10 years, and there is no significant increase in risk of thyroid cancer for those exposed after age 20 years. Radiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 17 publications
1
46
0
2
Order By: Relevance
“…10 Reports from studies of survivors of the Chernobyl accident have reported a high risk of thyroid cancer in children as a consequence of exposure to lowdose radiation. [6][7][8][9] As a result, thyroid carcinoma is a complication of irradiation even when the tissue lies outside the radiation field where the gland is exposed to scatter irradiation. The radiosensitivity of thyroid tissue coupled with the increased vulnerability of the paediatric gland accounts for the high incidence of thyroid carcinoma in childhood cancer survivor cohorts 23 as well as children who were exposed to radioactive contamination after the Chernobyl nuclear accident in 1986.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…10 Reports from studies of survivors of the Chernobyl accident have reported a high risk of thyroid cancer in children as a consequence of exposure to lowdose radiation. [6][7][8][9] As a result, thyroid carcinoma is a complication of irradiation even when the tissue lies outside the radiation field where the gland is exposed to scatter irradiation. The radiosensitivity of thyroid tissue coupled with the increased vulnerability of the paediatric gland accounts for the high incidence of thyroid carcinoma in childhood cancer survivor cohorts 23 as well as children who were exposed to radioactive contamination after the Chernobyl nuclear accident in 1986.…”
Section: Discussionmentioning
confidence: 99%
“…The radiosensitivity of thyroid tissue coupled with the increased vulnerability of the paediatric gland accounts for the high incidence of thyroid carcinoma in childhood cancer survivor cohorts 23 as well as children who were exposed to radioactive contamination after the Chernobyl nuclear accident in 1986. [6][7][8][9] Childhood cancer survivors who were under the age of 5 at the time of exposure to radiation therapy are reported to be at greatest risk and the risk remains comparatively higher for those under the age of 10 compared to older age groups. 10 In our study, risk was lowest in those aged more than 10 years when compared to the 5-9 and 0-4 year age groups: RR 1.0 (standard), 1.0 (0.4-2.2) and 0.5 (0.2-1.3), respectively although there was no significant difference.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Напом-ним, что для лечения дифференци рованного РЩЖ применяются гораздо более высокие разовые активности 131 I (100-200 мКи и выше) и до суммарной активности 600 мКи нет никаких данных о повышении риска радиа ционно индуцированных карцином и лейкемии, нарушении детородной функ-ции, врожденных аномалиях развития у по-томков [21,22]. Необходимо отметить, что накопленный мировой наукой опыт свиде-тельствует, что риск развития РЩЖ возни-кает после облучения ЩЖ (минимальный латентный период 5 лет, максимальный -30 лет) в малых дозах (0,05-25 Гр; 0,09-30 мкКи/г) и при условии непрерывного (повто ряющегося) облучения ЩЖ [23,24]. Это объяс няется накоплением абберантных и сублетальных повреждений ДНК, которые накапливаются и повышают риск развития РЩЖ.…”
Section: ключевые слова: радиойодтерапия дети подростки болезнь грunclassified